That is why you have an education go to school and learn your anwer.
Answer:
![P(x)=(x-2i)(x-3i)](https://tex.z-dn.net/?f=P%28x%29%3D%28x-2i%29%28x-3i%29)
Step-by-step explanation:
Build a Polynomial Knowing its Roots
If we know a polynomial has roots x1, x2, ..., xn, then it can be expressed as:
![P(x)=a(x-x1)(x-x2)...(x-xn)](https://tex.z-dn.net/?f=P%28x%29%3Da%28x-x1%29%28x-x2%29...%28x-xn%29)
Where a is the leading coefficient.
Note the roots appear with their signs changed in the polynomial.
If the polynomial has a leading coefficient of 1 and roots 2i and 3i with multiplicity 1, then:
![P(x)=1(x-2i)(x-3i)](https://tex.z-dn.net/?f=P%28x%29%3D1%28x-2i%29%28x-3i%29)
![\mathbf{P(x)=(x-2i)(x-3i)}](https://tex.z-dn.net/?f=%5Cmathbf%7BP%28x%29%3D%28x-2i%29%28x-3i%29%7D)
Answer:
x = 1 + i sqrt(7/2) or x = 1 - i sqrt(7/2)
Step-by-step explanation:
Solve for x:
2 x^2 - 4 x + 9 = 0
Divide both sides by 2:
x^2 - 2 x + 9/2 = 0
Subtract 9/2 from both sides:
x^2 - 2 x = -9/2
Add 1 to both sides:
x^2 - 2 x + 1 = -7/2
Write the left hand side as a square:
(x - 1)^2 = -7/2
Take the square root of both sides:
x - 1 = i sqrt(7/2) or x - 1 = -i sqrt(7/2)
Add 1 to both sides:
x = 1 + i sqrt(7/2) or x - 1 = -i sqrt(7/2)
Add 1 to both sides:
Answer: x = 1 + i sqrt(7/2) or x = 1 - i sqrt(7/2)
It may be misleading because it only tells you those two years, not what happened between those years
Step-by-step explanation:
I think the answer is 1 lemonade
Because it says to make lemonade not 2 or 3 lemonade